The effectiveness of developing popular scientific books on Anacardiaceae to improve students’ critical thinking skills - Dita Sifa Febriyanti; Yudi Firmanul Arifin; Aminuddin Prahatama Putra (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
The development of innovative local potential-based teaching materials in the Ethnobotany course of the Anacardiaceae family, which has not been fully implemented, causes student boredom while studying. It is necessary to develop popular scientific books (PSB) to help students understand learning material and significantly improve students' critical thinking skills. This development research aims to describe the expected and actual effectiveness of PSBs developed to enhance students' critical thinking skills. The research method used Tessmer's formative evaluation design. Research results on the effectiveness of expectations get an average value of 72.7%, and actual effectiveness is 77.35%. The average value of N-gain is 0.5, which is included in the medium criteria. The conclusion from the research results shows that the PSB on Ethnobotany of the Anacardiaceae family that was developed is effective in improving students' critical thinking skills so that students in Ethnobotany courses can use it. In general, the benefit of the results of this research is that development products based on local potential can be developed according to the needs of teaching materials and by the principles of critical thinking skills for students.Abstrak Pengembangan bahan ajar berbasis potensi lokal yang inovatif pada mata kuliah Etnobotani famili Anacardiaceae yang belum sepenuhnya dilakukan menyebabkan kejenuhan mahasiswa saat belajar. Perlu dikembangkan buku ilmiah populer (BIP) untuk membantu mahasiswa memahami materi pembelajaran sekaligus salah satu upaya dalam meningkatkan keterampilan berpikir kritis mahasiswa. Penelitian pengembangan ini bertujuan untuk mendeskripsikan keefektifan harapan dan aktual dari pengembangan BIP untuk meningkatkan keterampilan berpikir kritis mahasiswa. Metode penelitian menggunakan desain evaluasi formatif Tessmer. Hasil penelitian pada keefektifan harapan memperoleh nilai rata-rata 72,7% dan keefektifan aktual memperoleh nilai rata-rata 77,35%%. Nilai rata-rata N-gain sebesar 0,5 yang termasuk ke dalam kriteria sedang. Kesimpulan dari hasil penelitian menunjukkan bahwa BIP Etnobotani famili Anacardiaceae yang dikembangkan efektif untuk meningkatkan keterampilan berpikir kritis mahasiswa sehingga dapat digunakan mahasiswa pada matakuliah Etnobotani. Secara umum, manfaat dari hasil penelitian ini adalah produk pengembangan berbasis potensi lokal dapat dikembangkan sesuai dengan kebutuhan bahan ajar dan sesuai dengan kaidah keterampilan berpikir kritis untuk mahasiswa.